Penerapan Metode Simple Additive Weighting (SAW) untuk Pemilihan Calon Penerima Beasiswa pada SMPN 3 Kasihan - Safitri, Nurul Aulia; Gutama , Deden Hardan; Wijaya, Dhina Puspasari; Danianti, Dita (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Education is an important aspect of human life, because education is one of the supports for realizing a change in order to achieve progress in various sectors of life, such as in the economic, social, cultural and political sectors Currently the government has a free education program and has established a 12-year compulsory education program. To support the program, many government and private institutions provide educational assistance through scholarship programs. SMPN 3 KASIHAN gets a quota for its students to participate in scholarship programs from the government, one of which is the Smart Indonesia Program (PIP) scholarship. The selection process at SMPN 3 KASIHAN has not implemented a method and is still done manually. This research aims to build a web-based scholarship decision support system using the Simple Additive Weighting (SAW) method and apply the method according to the criteria set by SMPN 3 KASIHAN. System modeling uses the Unified Modeling Language (UML) and for design is used Use Case Diagram modeling tools, Activity Diagrams, and the programming language used is PHP. Based on the results of the discussion during the research, it is concluded that the system under study fulfills the initial objectives of the research, namely helping SMPN 3 KASIHAN in determining the appropriate scholarship recipient, so as to reduce errors in determining scholarship recipients.